PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DAN SIKAP SOSIAL TERHADAP PRESTASI BELAJAR PPKn (Studi Eksperimen pada Siswa kelas VII SMP Negeri 1 Pulau Pinang) - Rizki Agustina Pratiwi (UNIB Press, 2020)
This study aims to: Know the differences in PPKn learning achievement between students learning with the Jigsaw type cooperative learning model with the STAD type cooperative learning model, Know the difference between student achievement with high and low social attitudes, and determine the effect of the interaction of learning models and social attitudes towards learning achievement. The research method used was a squasi experimental research with 2 x 2 factorial design. The subjects of this study were students of class VII SMP Negeri 1 Pinang Lahat. Data collection methods in the study are learning achievement tests in the form of multiple choice and students' social attitude instruments. The results showed that: PPKn learning achievement among students who studied with the Jigsaw type cooperative learning model was higher than the STAD type cooperative learning model, PPKn learning achievement among students who had high social attitudes was better than students who had low social attitudes, and there is an interaction effect of learning models and social attitudes on student learning achievement PPKn